Analysis of Cancer Care Services: A Case Study Approach in the Eastern Cape Province, South Africa - Willie, Michael Mncedisi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the relationship between medication shortages and supply chain inefficiencies within the healthcare system, particularly in cancer care. Furthermore, it examines how logistical challenges, including delays and inadequate distribution networks, worsen the shortage of critical cancer medications, affecting patient access to essential treatments. Research Design and Methodology: To understand how these supply chain inefficiencies impact healthcare delivery in oncology, a qualitative approach incorporating a literature review and case studies is used. The study applies supply chain resilience theory to assess current logistics' effectiveness and identify areas for improvement. Findings and Discussion: The study highlights the significant role of supply chain inefficiencies in exacerbating medication shortages, which directly impact cancer patients' access to life-saving treatments. It underscores the need for better management practices, more efficient distribution systems, and enhanced logistics to address these issues. Implications: The study stresses the importance of strategic supply chain improvements to ensure the consistent availability of critical medications. The findings aim to guide healthcare policies and practices, particularly in oncology, to enhance patient care and improve healthcare outcomes. Addressing these inefficiencies will facilitate more reliable and timely access to cancer treatments, ultimately improving patient outcomes.